Number of Students in the Higher Education and the Students’ Motivation in the Further Higher Education (Training and Practice : Journal of Educational Sciences, 2007)
The study’s aim is to show how the number of students’ changed and grew from the 60s of the last century. The study explains how the education turned into a mass production and points out also the causes and consequences of the number growing. The lifelong-learning concept is mentioned as well, as a main ok of the growing. The economical situation makes people to study continously, because the labour market needs people, who are able to adapt to the labour market’s continously changing challenges. The Bologna process has been started in Hungary in 2006, so there is a need to examine the number of applicant students to the different universities, among them of the University of Pecs as well. In the second part of the study the author bemutat a survey, which was studying the students’ motivation in the further education. The survey was made among three universities in Hungary. The comparison of two universities participating in the survey was interesting. The main motivations of the students’ in the farther higher education are the following: professional interest to find a (new) job, to get a (new) diploma. Usually the students’ families give them the biggest incentive and help.